Medial rectus recession versus lateral rectus advancement in surgical correction of consecutive esotropia - Sahar H Elsayed; Omar El-Shabrawy Basyoni; Mohammad A El-Marakby; Riham S Attia (Delta Journal of Ophthalmology, 2022)
Background Following surgery to address intermittent exodeviation, consecutive esotropia (ET), in which postoperative ET continues for more than 6 months, may arise. Both lateral rectus advancement (LRA) and medial rectus recession (MRR) are effective in correction of consecutive ET. Purpose The aim of this study was to compare the results of LRA and MRR in correction of consecutive ET (within 40 PD) following bilateral lateral rectus recession for treatment of intermittent exotropia. Patients and methods This was a randomized double-blind controlled trial that included 30 patients who were divided into two groups: group 1 (LRA group, 15 patients) and group 2 (MRR group, 15 patients). Unilateral or bilateral LRA or MRR was done according to the preoperative angle of deviation. All patients had preoperative ocular examination, which included history taking, visual acuity testing, slit-lamp examination, fundus examination, preoperative angle of deviation at near and far using the Krimsky method, stereopsis using the Titmus test, and suppression using the Worth 4-dot test. The patients were followed up at 1, 3, and 6 months after surgery. Results There was no statistically significant difference between the two groups in the preoperative angle of deviation (P=0.213). In group 1, the mean preoperative angle of consecutive ET was 29.0±6.14 PD, which improved to 0.87±3.56 PD 6 months after surgery, with a statistically significant difference (P<0.001). In group 2, the mean preoperative angle of consecutive ET was 25.47±8.81 PD and improved to 1.67±4.58 PD 6 months after surgery, with a statistically significant difference (P<0.001). However, there was no statistically significant difference between the two groups in the postoperative angle of deviation (P=0.562). Six months postoperatively, there were two (13.3%) undercorrected cases and one (6.7%) overcorrected case, with a success rate of 80% in group 1, whereas in group 2, there were two (13.3%) undercorrected cases and two (13.3%) overcorrected cases, with a success rate of 73.4%, with no statistically significant difference between the two groups in the success rate (P=0.66). In group 1, the mean preoperative stereoacuity value was 291.7±206.5, which improved significantly postoperatively to 140±35.71 (P=0.005). Similarly, in group 2, the mean preoperative stereoacuity value was 506.7±810.5 and improved significantly postoperatively to 150±46.41, (P=0.003). Conclusion Both LRA and MRR were effective in the correction of consecutive ET.